Evaluating the productivity gap between commercial and traditional beef production systems in Botswana. (November 2016) - Temoso, Omphile; Villano, Renato; Hadley, David
Abstract: The beef cattle production system in Botswana is dualistic in structure in that it includes both traditional and commercial production systems, which are distinct from one another in terms of objectives, land tenure, technology, and management practices. The purpose of this paper is to measure the key performance indicators of beef cattle production systems in Botswana and explore the drivers of change in those indicators. We examine differences in productivity and production technologies between the two beef production systems. The results show that traditional farms are technically inefficient and that their technology lags behind that of commercial farms. The use of improved breeds, off-take rates and selling to the Botswana Meat Commission (which control the only exporting abattoirs in Botswana) were found to improve technical efficiency in the commercial production system, but only off-take rates had a positive effect on efficiency in the traditional production system. Both farming systems have the potential to overcome technology constraints and achieve the highest attainable productivity level through improvements in; beef cattle technologies, farmer capacity in production and marketing, and the effectiveness of the technology transfer process. Highlights: We measure the key performance indicators and drivers of beef cattle production systems in Botswana. We found significant differences in productivity and production technologies between traditional and commercial farms. Key drivers of productivity include the use of improved breeds, off-take rates and selling to the exporting abattoirs. There is potential to improve productivity through improved technologies and farmer capacity in production and marketing.